The effectiveness of POW + C-SPACE strategy provided by parents of children with writing difficulties on story-writing skills - Kürşat Öğülmüş (Journal of Pedagogical Research, 2021)
In this study, the POW + C-SPACE (Pick my idea-Organize my notes-Write and say more + Characters-Setting-Purpose-Action-Conclusion-Emotions) strategy developed on the basis of the self-regulated strategy development model (SRSDM) was presented through families to improve the story-writing skills of children with writing difficulties (WD) and its effects were evaluated. The study employed a multiple probe design with probe conditions across subjects, one of the single-subject research models. The study group consisted of three mothers and their children with WD. Mothers were taught the POW + C-SPACE strategy and were asked to present what they learned to their children at home. As a result of the study, it was concluded that when the POW + C-SPACE strategy was presented through parents, it was effective in developing the story-writing skills of children with WD.